2015
DOI: 10.1007/s13762-015-0888-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metals and rheological characteristics of coal ash samples in presence of some selective additives

Abstract: The huge quantity of coal ash produced in Indian thermal power plants is disposed of in ash landfills or ash ponds. The deposition of ash in ash ponds through conventional lean slurry form is viewed as a major potential release of many environmentally sensitive heavy metals due to possible contamination with ground water. An attempt has been made in this paper to assess the leachability of the heavy metals such as Cu, Pb, Ni, Co, Zn, Cd, Hg and As from two Indian power plant ash samples in the presence of some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This happens due to the formation of the additive layer over the surface of solid particles which prevents the leaching of traced elements. As the pH value of slurry suspension increases that contribute to the decreasing of leaching of traced elements (Pani et al 2016;Singh et al 2016). It was also found that the maximum reduction in the leaching concentration rate of all traced elements in bottom ash samples was found with 0.4% addition of additive whereas marginal reduction was observed with 0.2% and 0.6%.…”
Section: Resultsmentioning
confidence: 82%
“…This happens due to the formation of the additive layer over the surface of solid particles which prevents the leaching of traced elements. As the pH value of slurry suspension increases that contribute to the decreasing of leaching of traced elements (Pani et al 2016;Singh et al 2016). It was also found that the maximum reduction in the leaching concentration rate of all traced elements in bottom ash samples was found with 0.4% addition of additive whereas marginal reduction was observed with 0.2% and 0.6%.…”
Section: Resultsmentioning
confidence: 82%
“…Our diets include many substances which can cause fatigue and exhaustion. Taken regularly, Aloe vera juice ensures a greater feeling of well-being, allowing energy levels to increase and also helps maintain a healthy body weight, (Lad et al, 2013;Kumbhar et al, 2015;Pani et al, 2016)…”
Section: Increases Energy Levelsmentioning
confidence: 99%
“…Co-disposal of different kinds of waste without knowing their leaching characteristics may pose a threat to environment, for example, the disposal of ash in an acidic environment increased the leaching of heavy metals and contaminated the ground water at the disposal site [9]. For this reason, leaching/extraction tests are commonly applied because they provide information about the potential release of constituents from solid materials to the liquid phase [10].…”
Section: Introductionmentioning
confidence: 99%